Gain-of-function mutations and immunodeficiency: at a loss for proper tuning of lymphocyte signaling. Issue 6 (December 2015) - Arjunaraja, Swadhinya; Snow, Andrew L.
Abstract : Purpose of review: To present recent advances in the discovery and characterization of new immunodeficiency disorders linked to gain-of-function (GOF) mutations in immune signaling molecules. Recent findings: In the past 2 years, extensive cellular and molecular studies have illuminated the root causes of pathogenesis for several new monogenic primary immunodeficiency disorders (PIDs) linked to GOF mutations in signaling molecules. Here we discuss on two disorders (BENTA and APDS/PASLI) featuring shared clinical presentation (e.g. lymphoproliferation, selective antibody deficiencies, recurrent sinopulmonary infections). These findings highlight an emerging theme: both loss-of-function and gain-of-function mutations in key molecules can disrupt finely tuned immunoreceptor signaling modalities, resulting in the dysregulation of lymphocyte differentiation and impaired adaptive immunity. Summary: Continued research on the molecular pathogenesis of PIDs defined by hyperactive signaling molecules will better distinguish these and related disorders, and pinpoint tailored therapeutic interventions for 'retuning' the immune response in these patients.